Japan’s Military Transformation in Abe Era: A Revolution or Something Else? - Wicaksono, Ganesh Aji; Chairil, Tangguh (Journal of Strategic and Global Studies, 2025)
After the World War II, Japan has been adopting a pacifist Constitution and established the Japan Self-Defense Forces (JSDF) for narrow self-defense operations. The JSDF are restricted from having offensive military weapons. However, Japan’s pacifism and restrained security policy have been evolving recently, especially during the term of Prime Minister Shinzo Abe (2012-2020). The latest example is Japan’s plan to enable forward defense and counterstrike. This paper explores the transformation of Japan’s military through the revolution of military affairs (RMA) concept. The findings suggest evolutionary transformation of Japan’s military rather than revolutionary. The factors explored include international and domestic factors. The international factors include Japan’s threat perception and its desire to be more active participant to maintain international stability. The domestic factors include Japan’s constitutional limits, Abe’s reinterpretation of the constitutional limits, and remaining pacifism at the parliament.